Neoseiulus californicus McGregor: A Predatory Mite Species for Controlling Twospotted Spider Mites in Strawberries - Silvia I. Rondon; James F. Price; Oscar E. Liburd; Roger Francis; Daniel J. Cantliffe (EDIS)
Neoseiulus californicus McGregor (Acari: Phytoseiidae) is an oblong, tiny, mobile, predatory mite that feeds on a variety of prey (Fig. 1). It belongs to the suborder Acariforme in the Acari order. The division includes more than 30,000 described species included in the ancient group of Arachnida (Krantz, 1978). This document is HS1001, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: November 2004.